Komunikasi Krisis pada Pemberitaan Covid-19 di Media Sosial Facebook (Studi Kasus pada Masyarakat Desa Kunduran, Seluma Timur) - Yudi Marihot; Sapta Sari; Anis Endang (Jurnal Multidisiplin Dehasen (MUDE), 2022)
The purpose of this study is to find out about crisis communication in the news of covid-19 on social media Facebook in the Kunduran village community, Seluma Timur. . In this study, the authors used qualitative research. Bogdan and Taylor define qualitative research methods as research procedures that produce descriptive data in the form of written or spoken words from people and observable behavior. The people of Kunduran Village have the view that the news of covid-19 on social media facebook circulating is mostly news made up by certain people so that the truth cannot be accounted for. Therefore, people who use social media Facebook as a means to find information about COVID-19 must choose and sort out the correct news from trusted sources, such as on the Indonesian Ministry of Health's Facebook page.